Frequency Domain Modeling of a Halbach PM Linear Generator Based Two-Body Point Absorber for Wave Energy Conversion - Tan, Yimin; Liu, Na; Lin, Kejian; Zhang, Zuguang (Frontiers in Energy Research, 2020)
Point absorbers utilize the relative motion between the floating body and the submerged body to harvest the wave energy. This paper presents the parametric study of a two-body wave energy point absorber to investigate the influence of key design factors. The targeting point absorber employs a slotless Halbach linear generator as the power take-off system to improve the energy conversion efficiency. In this work, we have linearized our developed nonlinear time domain model and presented it in frequency domain to improve the simulation efficiency, where the results of the time domain model and the frequency domain model have been compared. The stochastic linearization method is employed for the first time to linearize the nonlinear dragging effect of a point absorber. The case study suggests that the stiffness of the power take-off system and viscous floater dragging coefficient should be as small as possible and the optimal mass of the bodies should be adopted to achieve the maximum power output. Under the irregular wave condition, the power matrix against the wind speed and the damping coefficient of the power take-off system shows that the optimal damping coefficient is determined by the local weather and geographic condition. Regarding the determinants of the damping coefficient, the factors that affect the power take-off system is investigated. The Halbach PM array length and the coil width should be specially optimized to obtain the desired damping coefficient of the power take-off system at a given point absorber dimension. Lastly, a test-rig has been developed to validate the magnetic domain model.